A Review: Phytochemical Investigation and Medicinal Applications of Herb’s - Padole, Nitin; Chandankhede, Himanshu; Deshmukh, Rupal; Chatakwar, Prajakta; Dandekar, Shivani; Baheti, Jagdish (Asian Journal of Pharmaceutical Research and Development, 2022)
Now a day’s major population over the world is facing the issue of allopathic drug and their adverse effect in treatment of various diseases. Ayurveda is one of the traditional medicinal systems of India. The philosophy behind Ayurveda is preventing unnecessary suffering and living a long healthy life. Herbal medicines have existed world-wide with long recorded history and they were used in ancient Chinese, Greek, and Indian medicine for various therapies purposes.Herbals are one of the best alternativesin treatment of acute and chronic diseases. In this review different herb has been studied due to its medicinal, pharmacognostic and therapeutic application. This article enlists some commercial and non-commercial Polyherbal all around the world. In which plants, fruits, leaves, seeds and powder of Momordica dioica, Lantana camara L., Curcuma longa,Carthamustinctorius and Acacia catechu has been studied. This article provides a general idea about different herbs, their phytochemical contents, method of extraction and applications in treatment of various diseases.